Closing the Gap in the Paris Rulebook: Assessing Ways to Advance the Environmental Integrity of Carbon Markets under Article 6 of the Paris Agreement - Barlaup, Asgeir (Tufts Archival Research Center, 2020)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy.; This thesis argues that environmental integrity has evolved into a multi-dimensional issue which requires a generic approach, distinct from the dichotomous definition under the Kyoto era which largely centered on fulfillment of the additionality criteria. This revised definition is used to arrive at a novel analytical framework which is applied as a measuring rod to compare the negotiation positions of four countries and one coalition with different levels of involvement and experience using the market-based approaches of the Kyoto Protocol.